Use of Seaweed (Eucheumacottonii) as a Substitute for Carrageenan in Making Jelly Drink Rosella (Study of Seaweed and Carrageenan Concentration) - Indah Wati; Ida Agustini Saidi (Universitas Muhammadiyah Sidoarjo, 2015)
This study aimed to determinethe concentration effect of carrageenan and seaweed on the quality of rosella jelly drink. The experiment was arranged using a randomized block design (RBD), which consists of 9 treatment that carrageenan concentration were 0.40%, 0.50% and 0.60%; and seaweed concentration were 8%, 9%, 11%, 12%, and 13%. The experiments were repeated three times to obtain 27 units of the experiments. The measured variableswere physical analysis (viscosity), chemical (dietary fiber and pH) and organoleptic (taste, aroma, color and texture). The data of physical-chemical properties were analyzed by ANOVA followed by HSD test, while the organoleptic data were analyzed using Friedman test and determining the best treatment based on effectiveness index (De Garmo). The results showed that: the proportion of carrageenan and seaweed with roselle juice significantlydifferent on the viscosity, taste, color and texture of the jelly drink roselle, but not significantly different on levels of dietary fiber, pH and aroma of rosella jelly drink. The best quality of rosella jelly drinkwas obtained from 0.50% carrageenan concentration with the following characteristics: viscosity 6.23%, 0.40% dietary fiber, pH 3.24, 5.40 flavor (rather like), aroma 4.43 (plain), color 4.87 (regular), viscosity 5.43 (somewhat like). The best seaweed treatment on this study is the treatment concentration of 8% with the following characteristics: viscosity 6.15%, 0.44% dietary fiber, pH 3.38, 4.90 flavors (regular), aroma 4.30 (regular), color 4.97 (regular), viscosity 4.00 (regular).